SYNERGY OF DIGITAL TECHNOLOGIES AND FINTECH SOLUTIONS IN MODERNISING THE MANAGEMENT OF AGRICULTURAL ENTERPRISES (INNOVATIVE ECONOMY, 2026)
Kostetskyi V.V., Butov A.M. SYNERGY OF DIGITAL TECHNOLOGIES AND FINTECH SOLUTIONS IN MODERNISING THE MANAGEMENT OF AGRICULTURAL ENTERPRISES Purpose. The aim is to provide a scientific substantiation of the role and potential of integrating digital technologies and FinTech solutions (Agri-FinTech) in the management system of agricultural enterprises, determining their impact on the efficient use of land resources, financial stability and competitiveness of economic entities, as well as developing practical approaches to integrating such tools into the activities of the agricultural sector.Methodology of research. The methodological foundation of this study is a combination of general scientific and specialized methods, which enabled a comprehensive analysis of the processes of digitizing land resource management in the context of Agri-FinTech development. In particular, a systematic approach was used to substantiate the interconnection between digital technologies, financial instruments, and land resource management as a single integrated ecosystem. Analysis and synthesis were applied in the study of modern digital tools and the determination of their role in improving the efficiency of land use. The comparative method was used to contrast traditional and digital approaches to land asset management and financing of the agricultural sector. Methods of generalization and systematization made it possible to formulate the concept of Agri-FinTech as an integrated direction for the development of the agricultural economy. The economic and analytical method was applied to assess the impact of digital and FinTech solutions on the efficiency of land resource management and the reduction of transaction costs. The logical method was used to substantiate the cause-and-effect relationships between digitalization, financing, and the enhancement of agricultural enterprises’ sustainability.Findings. It has been determined that the synergy of digital technologies (GIS, remote sensing, Big Data, artificial intelligence, cloud platforms, digital cadastres) and FinTech solutions (digital lending, smart contracts, blockchain, asset tokenisation, index agricultural insurance) forms a fundamentally new model of agricultural enterprise management. This combination makes it possible to automate land transactions, ensure transaction transparency, improve land valuation accuracy, expand access to financing, optimise production processes, and increase the sustainability of agribusiness. The article identifies key barriers and directions for the development of Agri-FinTech in the context of military challenges and economic uncertainty.Originality. It is substantiated that the integration of digital agricultural technologies and financial instruments within the Agri-FinTech framework creates a new paradigm for land resource management which, unlike traditional approaches, is based on the use of real-time data, transaction automation, and asset tokenization, which makes it possible to increase the transparency of land relations, reduce risks, and expand access to financing for agricultural enterprises. Scientific and methodological approaches to managing the land bank of agricultural enterprises have been improved through the integration of GIS technologies, satellite monitoring, Big Data, and artificial intelligence with FinTech solutions, ensuring greater accuracy in the valuation of land assets and the effectiveness of management decisions. The theoretical rationale for the use of blockchain technologies and smart contracts in land relations has been further developed, particularly regarding the automation of lease transactions, ensuring the immutability of cadastral data, and the formation of transparent supply chains for agricultural products.Practical value. The proposed Agri-FinTech tools can be used by agricultural enterprises, financial institutions, investors to increase the efficiency of land bank management of enterprises, optimize financial transactions, reduce risks, improve leasing processes, assess and monitor land assets; as well as by public administration bodies when developing policies for the digital transformation of the agricultural sector.Key words: Agri-FinTech, digital technologies, blockchain, smart contracts, tokenisation, GIS, Big Data, land resource management, agricultural enterprises, digital transformation.
Keywords: Agri-FinTech; digital technologies; blockchain; smart contracts; tokenisation; GIS; Big Data; land resource management; agricultural enterprises; digital transformation